DMAIC Based Approach for Analyzing and Controllling Defective Product in Rubber Clutch Damper Product: [DMAIC Based Approach for Analyzing and Controllling Defective Product in Rubber Clutch Damper Product] - Nata, Christopher; Tandika, Tegar; Rahayu, Priskila Christine (Universitas Pelita Harapan, 2025)
Rejects represent a major quality issue in the production process. If not effectively mitigated, they can increase production costs, disrupt process flow, and reduce customer satisfaction. This study aimed to minimize product rejection in rubber clutch damper manufacturing by applying the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) methodology. In the Define phase, Critical to Quality (CTQ) characteristics were identified to determine key improvement priorities. The Measure phase involved data collection to calculate Defects per Million Opportunities (DPMO), sigma level, and the construction of a Pareto chart to highlight the dominant sources of defects. Subsequently, the Analyze phase employed Failure Mode and Effects Analysis (FMEA) to evaluate the Severity, Occurrence, and Detection of potential failures, leading to the determination of the Risk Priority Number (RPN) as a basis for improvement prioritization. In the Improve phase, corrective actions targeting the highest RPN factors were implemented, followed by the Control phase, which established sustainability through One Point Lessons and Standard Operating Procedures (SOPs). The implementation of the DMAIC framework resulted in a substantial improvement in process capability, indicated by an increase in sigma level from 4.11 to 4.58, and a reduction in the total production rejection rate from 1.51% to 0.31%. A paired t-test confirmed a statistically significant difference between pre- and post-improvement rejection rates (t = 61.63, p < 0.0001), leading to the rejection of the null hypothesis. These findings demonstrate that the applied improvements effectively reduced product defects and achieved a total rejection rate below the company’s management target of 0.40%. The study confirms the effectiveness of the DMAIC approach in enhancing product quality and operational efficiency within rubber component manufacturing. Bahasa Indonesia Abstract: Permasalahan reject merupakan salah satu isu krusial dalam proses produksi yang apabila tidak segera ditangani, dapat berdampak pada peningkatan biaya produksi, keterlambatan pengiriman antarproses, serta penurunan tingkat kepuasan pelanggan. Penelitian ini bertujuan untuk menurunkan tingkat reject pada produk rubber clutch damper melalui penerapan metodologi Six Sigma dengan pendekatan DMAIC (Define, Measure, Analyze, Improve, Control). Pada tahap Define, dilakukan identifikasi Critical to Quality (CTQ) untuk menentukan karakteristik yang berpengaruh signifikan terhadap kualitas produk. Tahap Measure meliputi pengumpulan data produksi guna menghitung nilai Defects Per Million Opportunities (DPMO), tingkat sigma, serta penyusunan diagram Pareto untuk mengidentifikasi jenis cacat dengan kontribusi terbesar terhadap total reject. Selanjutnya, tahap Analyze dilaksanakan menggunakan metode Failure Mode and Effects Analysis (FMEA) dengan penilaian terhadap parameter Severity, Occurrence, dan Detection, yang dikalikan untuk memperoleh nilai Risk Priority Number (RPN) sebagai dasar prioritas tindakan perbaikan. Tahap Improve difokuskan pada penerapan solusi korektif terhadap faktor penyebab dengan nilai RPN tertinggi, sedangkan tahap Control menitikberatkan pada keberlanjutan hasil perbaikan melalui penyusunan One Point Lessons (OPL) dan Standard Operating Procedures (SOP). Penerapan metodologi DMAIC menghasilkan peningkatan kapabilitas proses dengan kenaikan nilai sigma dari 4,11 menjadi 4,58, serta penurunan rejection rate total produksi dari 1,51% menjadi 0,31%. Hasil uji paired t-test menunjukkan perbedaan yang signifikan antara tingkat rejection rate sebelum dan sesudah perbaikan (t = 61,63; p < 0,0001), sehingga hipotesis nol ditolak. Dengan demikian, penerapan DMAIC terbukti efektif dalam menurunkan tingkat reject secara signifikan hingga di bawah target manajemen sebesar 0,40%, sekaligus meningkatkan kualitas produk dan efisiensi proses produksi.